Games of Strategy on the Renaissance Stage: A Game Theory Analysis of Ben Jonson’s Volpone - Dawood, Samir Talib (Thi Qar Arts Journal, 2025)
This study presents an analysis of Ben Jonson’s Volpone (16606) using game theory. It argues that this kind of analysis would yield new readings of the play. While the traditional criticism of the play focused on issues of morality and greed, an analysis inspired by game theory will shed light on issues of rationality (or the lack thereof) of characters’ actions. Instead of looking at characters in terms of tricksters and dupes, it will treat characters as players of strategic games who are trying to maximise their payoffs and minimise their costs. Besides, game theory can also help explain the process of theatrical communication in a new light. Moreover, by highlighting zero-sum games and the absence of equilibria in the interactions among characters, the analysis can account for the dark, almost tragic nature of the play.